El trabajo decente desde los lineamientos de la organización internacional del trabajo y su aplicabilidad en el sector agrìcola (2020)
Referring to "decent work" implies thinking not only about the significant burden that follows from the concept, but even more about the applicability, sustainability and guarantee that derive from legal systems in order to dignify both the trade and the worker. In this sense, this article refers to specific guidelines of the International Labour Organization in terms of social protection and promotion of labor rights, more generation of quality jobs, sustainable and finally social dialogue, aspects that have been subsumed in our internal regulations and therefore patents in the application of these provisions, especially in labor matters. In this way and supported in the legal field, it is hypothesized that the applicability of what "decent work" means in the workers of the agricultural sector, is still deficient, nevertheless, of being a normative requirement. To achieve this goal, the subject is approached from a qualitative-descriptive analysis which allows to enter more objectively in the understanding of the phenomenon.